Broers, Europe Under Napolean, 1799-1815 - Gutman, Sanford (Teaching History: A Journal of Methods, 2000)
Do we need yet another book on Napoleon? Michael Broers answers, not exactly. According to Broers, what we need, and indeed what he has given us, is a sophisticated historical analysis of the impact of Napoleonic rule on conquered Europe from the point of view of the ruled. So, if you are looking for a book primarily on Napoleon the man and ruler, or one on France under Napoleon, you will need to look elsewhere.